Testing of co-fermentation of poultry manure and corn silage = Badania ko-fermentacji obornika drobiowego i kiszonki z kukurydzy - Jędrczak, Andrzej; Królik, Dariusz; Sadecka, Zofia; Myszograj, Sylwia; Suchowska-Kisielewicz, Monika; Bojarski, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development of the production of poultry meat is connected with an increase in the quantity of the manure. The chemical characteristics predisposes this waste to processing by methane fermentation method. This study investigated the influence of ammonia and volatile fat acids on mesophilic anaerobic digestion of poultry manure.
Keywords: metan; obornik drobiowy; fermentacja metanowa; kiszonka z kukurydzy; methane; poultry manure; digestion; corn silage